Antioxidant activity and phytochemical investigation on Pereskia bleo (kunth) D. C. (jarum tujuh bilah) / Nor Aziyah Bakhari, Ainnie Rahayu Abdullah and Hasnah Osman - Bakhari, Nor Aziyah; Abdullah, Ainnie Rahayu; Osman, Hasnah (2009)
Phenolic, flavonoid and tannin content of dried Pereskia bleo were investigated using the well established method via UV-Vis Spectrometry. Pereskia bleo has phenolic content the highest followed by flavonoid and tannin content. A study of antioxidant activities of dried sample of Pereskia bleo was carried out by using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. The plant shows moderate antioxidant activity. Pereskia’s leaves from ethyl acetate extract showed the highest antioxidant activity (66.32 %) followed by Pereskia’s leaves from methanol extract (61.76 %). The total phenolic content showed a good correlation with antioxidant activity but not the total flavonoid and tannin content.